Executive health checkup package at All India Institute of Medical Sciences, Bhubaneswar: A novel approach - Bimal Kumar Sahoo; Manish Taywade; Vikas Bhatia; Binod Kumar Patro; Sachidananda Mohanty (Indian Journal of Community and Family Medicine, 2021)
Early detectionof a disease leads to relatively simple courses of treatment and prevents life-threatening complications. Many health conditions can be corrected or maybe improved through treatment modalities if they are discovered by health screening facilities. Health screening program such as executive health checkup is convenient, affordable, inexpensive, and vastly beneficial for the patients. Hence, health screening saves lives immensely by early detection of diseases and preventing serious complications. It is an effective component of healthcare. It achieves more positive effects than medical treatment and at a lower cost. Health promotion is aimed at influencing people's social circumstances and lifestyles so that their health is improved (or maintained) and disease is prevented.